MR Imaging Findings of Rathke’s Cleft Cysts: Significance of Intracystic Nodules - Byun, Woo Mok; Kim, Oh Lyong; Kim, Dong sug (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Rathke’s cleft cysts often may be difficult to differentiate from other intrasellar or suprasellar masses on radiologic studies. The purpose of this study was to describe the significance of intracystic nodules, a diagnostic characteristic found in Rathke’s cleft cysts, on MR images.METHODS: A retrospective review of MR studies was conducted for 13 patients who, after pathologic analysis, were diagnosed as having Rathke’s cleft cyst. These patients underwent unenhanced and contrast-enhanced T1- and T2-weighted axial and coronal spin-echo sequential imaging. The signal intensity and incidence of the intracystic nodules on T1- and T2-weighted images were analyzed. The signal intensity of the nodule was compared with that of white matter and surrounding cyst fluid. The signal intensity of cyst fluid was compared with the intraoperative appearance of the cyst fluid. Biochemical and pathologic analyses of the intracystic nodules were conducted in two cases.RESULTS: An intracystic nodule having high signal intensity on T1-weighted images and low signal intensity on T2-weighted images was observed in 10 (77%) of the cases. At surgery, intracystic nodules were yellow, waxy, solid masses. Pathologic analysis showed this nodule to be a mucin clump. Biochemical analysis of the intracystic nodules showed cholesterol and proteins as the main constituents. In the Rathke’s cleft cyst with intracystic nodules, cyst fluid revealed low signal intensity to isointensity relative to the intensity of the nodules on T1-weighted images, and isointensity to high signal intensity on T2-weighted images. Intracystic nodules were clearly visible on T2-weighted images.CONCLUSION: Because cyst fluid of Rathke’s cleft cysts shows variable intensities on MR images, the specific diagnosis is often difficult when based on MR signal intensity values alone. The presence of an intracystic nodule with characteristic signal intensities on MR images may be indicative of the diagnosis of Rathke’s cleft cyst.